How Does Education Improve Cognitive Skills? - Instructional Time versus Timing of Instruction - Sarah Dahmann (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2015)
This paper investigates two mechanisms through which education may affect cognitive skills in adolescence: the role of instructional quantity and the timing of instruction with respect to age. To identify causal effects, I exploit a school reform carried out at the state level in Germany as a quasi-natural experiment: between 2001 and 2007, the academictrack high school (Gymnasium) was reduced by one year in most of Germany's federal states, leaving the overall curriculum unchanged. To investigate the impact of this educational change on students' cognitive abilities, I conduct two separate analyses: first, I exploit the variation in the curriculum taught to same-aged students at academictrack high school over time and across states to identify the effect of the increase in class hours on students' crystallized and fluid intelligence scores. Using rich data on seventeen year-old adolescents from the German Socio-Economic Panel (SOEP) study, the estimates show that fluid intelligence remained unaffected, while crystallized intelligence improved for male students. Second, I compare students' competences in their final year of high school using data from the German National Educational Panel Study (NEPS). The results suggest that students affected by the reform catch up with their non-affected counterparts in terms of their competences by the time of graduation. However, they do not provide any evidence for the timing of instruction to matter in cognitive skill formation. Overall, secondary education therefore seems to impact students' cognitive skills in adolescence especially through instructional time and not so much through agedistinct timing of instruction.
Keywords: I21; I28; J24; 330; Cognitive Skills; Crystallized Intelligence; Fluid Intelligence; Skill Formation; Education; High School Reform